Refractive index matched liquid crystal cell for laser metrology application. Issue 11 (2nd September 2018) - Miszczyk, Emilia; Mazur, Rafał; Morawiak, Przemysław; Mrukiewicz, Mateusz; Piecek, Wiktor; Raszewski, Zbigniew; Kula, Przemysław; Kowiorski, Krystian; Kędzierski, Jerzy; Zieliński, Jerzy
ABSTRACT: There exists a problem in advanced numerically controlled automatic laser metrology. Reported study is related to minimising the system generating three or more coherent laser measuring beams. These rays, generated in a proper rangefinder, are necessary to determine the spatial coordinates and spatial orientation of the measured details. The simplest solution is to generate laser coherent light beams of wavelength λ  = 0.6328 µm with a given light polarisation plane and then to direct them along three or more independent optical paths. To form these optical paths, a special refractive index matched liquid crystal cell (MLCC) might be applied. To ensure a stable laser operation during the measurement process, the back reflection of the laser beam from MLCC should not exceed 0.7%. The main task of this work is developing such a MLCC transducer. To reach the critical back reflection low enough, the MLCC is constructed as multilayer structure. MLCC operates in positive twisted nematic (TN) mode. Owing to the high-birefringence nematic liquid crystal mixture used and rather big cell gap, the elaborated low reflective MLCC (with R  < 0.7%) works at TN mode above the sixth interference maximum of transmitting linearly polarised light. Graphical Abstract: